Phase-contrast imaging of multiply-scattering extended objects at atomic resolution by reconstruction of the scattering matrix - Pelz, Philipp M.; Brown, Hamish G.; Stonemeyer, Scott; Findlay, Scott D.; Zettl, Alex; Ercius, Peter; Zhang, Yaqian; Ciston, Jim; Scott, M. C.; Ophus, Colin (Physical Review Research, 2021)
Three-dimensional phase-contrast imaging of multiply-scattering samples in x-ray and electron microscopy is challenging due to small numerical apertures, the unavailability of wave front shaping optics, and the highly nonlinear inversion required from intensity-only measurements. In this work, we present an algorithm using the scattering matrix formalism to solve the scattering from a noncrystalline medium from scanning diffraction measurements and simultaneously recover the illumination aberrations. We demonstrate our method experimentally in a scanning transmission electron microscope, recovering the scattering matrix of a heterogeneous sample with two layers of multiwall carbon nanotubes filled with TaTe2 core-shell structures, spaced 10nm apart in the axial direction. Our work enables phase contrast imaging and materials characterization in multiply-scattering samples at high resolution for a wide range of materials.
CRIS-Team Scopus Importer:2022-07-19